2021
DOI: 10.1063/5.0046305
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of direct and indirect bandgaps in synthetic ultrathin MoS2 and WS2 films from photoconductivity spectra

Abstract: Exploring the thickness-dependent electronic properties of ultrathin transition metal dichalcogenides is crucial for novel optoelectronic devices. Particularly important is experimental information regarding the bandgap width. This information is scarce and often inconsistent among the several measurement techniques that were employed for this task, such as optical absorption, scanning tunneling spectroscopy and photoconductivity. Here, we present photoconductivity measurements in large-area synthetic MoS 2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…It is an n-type semiconductor with a band gap ranging from 1.2 eV for the bulk MoS 2 (indirect band gap) to 1.83 eV for the monolayer MoS 2 (direct and wider band gap). 17 Indeed, the bandgap of TMD materials depends on the number of their atomic layers, which provides different possibilities for their application in various fields such as optoelectronics, 18 solar cells, 19 photocatalysis and gas sensors. 20 It was reported that a high quality monolayer fit well with FET devices, whereas few layer TMDs are suitable for gas sensing applications.…”
Section: Introductionmentioning
confidence: 99%
“…It is an n-type semiconductor with a band gap ranging from 1.2 eV for the bulk MoS 2 (indirect band gap) to 1.83 eV for the monolayer MoS 2 (direct and wider band gap). 17 Indeed, the bandgap of TMD materials depends on the number of their atomic layers, which provides different possibilities for their application in various fields such as optoelectronics, 18 solar cells, 19 photocatalysis and gas sensors. 20 It was reported that a high quality monolayer fit well with FET devices, whereas few layer TMDs are suitable for gas sensing applications.…”
Section: Introductionmentioning
confidence: 99%
“…The reported band gaps of MoS 2 depend on the number of layers, deposition method, characterization techniques, etc. 10,55 We use a typical value (1.8 eV) of the band gap for 1L MoS 2 . 56,57 The conduction-band edge can be calculated knowing the band gap and valence-band edge.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The 10-nm-thick dielectrics used here is thick enough to screen the contribution from the underlying substrates. The reported band gaps of MoS 2 depend on the number of layers, deposition method, characterization techniques, etc. , We use a typical value (1.8 eV) of the band gap for 1L MoS 2 . , The conduction-band edge can be calculated knowing the band gap and valence-band edge. Figure b shows the band alignment extracted by XPS with core-level calibration to include the effect of the interface dipole , (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations